The Comparative Removal of Chromium and Cadmium Ions from Aqueous Solutions Using Silica Support Immobilized with 3-Aminopropyl Trimethoxysilane Salicylate - Kenneth O. Amanze; Janet O. Amanze; Appolinus I. C. Ehirim; Lynda C. Ngozi-Olehi; Rosemary I. Uchegbu; Glory J. Okore; Pamela I. Okeke; Christian E. Enyoh (Physchem)
A 3-Amino-Propyl Trimethoxy Silane (APTS) functionalized silica was prepared and investigated. The functionalized silica showed a powerful removal behavior towards Chromium (III) [Cr (III)] and Cadmium (II) [Cd (II)] ions in aqueous solution. Different factors affecting the heavy metal ions adsorption on these substrates such as pH, initial concentration, contact time, and temperature were investigated. FT-IR analyses were carried out to characterize the functionalization of salicylaldehyde unto 3-aminopropyl silica. Results showed that optimum adsorption of the metal ions occurred at a pH of 7 and 6 by the pure silica and functionalized silica, respectively. Removal efficiencies of the adsorbents showed the trend: Salicylaldehyde-APTS modified > pure silica. The adsorption was described by the Langmuir adsorption isotherm. The kinetic results showed that the adsorption was described well with the pseudo second-order kinetic model. The study reveals that both pure silica and functionalized silica can be used as good adsorbents for the removal of the heavy metal pollutants from aqueous solutions and may be applied in the treatment of industrial waste waters, and they may be useful in detoxifying our already polluted environments.